2013
DOI: 10.1152/japplphysiol.00738.2013
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxy-β-methylbutyrate (HMB)-free acid attenuates circulating TNF-α and TNFR1 expression postresistance exercise

Abstract: The purpose of this study was to examine the effect of β-hydroxy-β-methylbutyrate-free acid (HMB-FA) and cold-water immersion (CWI) on circulating concentrations of TNF-α and monocyte TNF-α receptor 1 (TNFR1) expression. Forty resistance-trained men (22.3 ± 2.4 yr) were randomized into four groups [placebo (PL), HMB-FA, CWI, and HMB-FA-CWI] and performed an acute, intense exercise protocol (four sets of up to 10 repetitions of the squat, dead lift, and split squat). Participants also performed four sets of up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 53 publications
10
50
0
Order By: Relevance
“…HMB supplementation increased circulating IL-4 by 19.75% immediately after heavy RE in resistance-trained men, which may be attributed to anti-inflammatory effect of HMB that supported by previous studies [6,24,25]. Consistent with our findings, previous study has shown that HMB exerts anti-inflammatory effect by attenuating elevations in circulating TNF-α immediately after acute bout of heavy RE and as well as reducing TNFR1 expression on human monocytes at 30 min post RE [6].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…HMB supplementation increased circulating IL-4 by 19.75% immediately after heavy RE in resistance-trained men, which may be attributed to anti-inflammatory effect of HMB that supported by previous studies [6,24,25]. Consistent with our findings, previous study has shown that HMB exerts anti-inflammatory effect by attenuating elevations in circulating TNF-α immediately after acute bout of heavy RE and as well as reducing TNFR1 expression on human monocytes at 30 min post RE [6].…”
Section: Discussionsupporting
confidence: 91%
“…Tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), IL-1 and C reactive protein (CRP) are considered as low grade systemic inflammatory cytokines [4]. Studies examining the acute effect of RE on inflammatory markers revealed significant elevations [5,6] and no changes [2,7] in inflammatory cytokines. The inflammatory responses to a single bout of RE may be due to RE-induced muscle damage [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations